Evaluation of the Effect of Scenario writing on the Clinical Reasoning Ability of Medical Trainees in the Internal Rotation using KF and DTI Methods - roghayeh akbari; seyed kamran soltani arabshahi; alireza monajemi (Babol University of Medical Sciences, 2022)
Background and Objective: Clinical reasoning is one of the important categories in medicine and teaching it in different ways can accelerate the student's ability to approach expert professional thinking. In addition, complementary trainings, along with clinical training, can promote clinical training in pandemics and situations where contact with the patient is reduced for some reason. Methods: This is an semi-experimental, case observation study in which the case group was trained in clinical reasoning by scenario writing method, and after the test, 2 groups were compared with KF and DTI tests. The two were identical based on their basic science test scores before the study.  Findings: In this study, 60 people in two groups of case and control (30 people in each group) were compared with DTI and KF tests. The average DTI score in the case group was 151.4±15.3 and the average score in the control group was 151.8±17.2, the scores in both the case and control groups were not significant (P-value=0.922). The KF scores were 36.3±4.5 in the control group and 30.2±8.2 in the case group, and the scores in the case group were significantly higher than the control group (P-value=0.001) Conclusion: The results of the study showed that short-term scenario writing training can be effective in improving the KF score and clinical reasoning, but increasing the DTI score requires more training time.